Relationship of Major Histocompatibility Complex Class II Genes to Inhibitor Antibody Formation in Hemophilia A - Lippert, Lloyd E; Fisher, Lyman Mc A; Schook, Lawrence B (Thrombosis and Haemostasis, 1990)
Approximately 14% of transfused hemophiliacs develop an anti-factor VIII inhibitory antibody which specifically neutralizes factor VIII procoagulant activity. In this study an association of the major histocompatibility complex (MHC) with inhibitor antibody formation was evaluated by restriction fragment length polymorphism (RFLP) analysis using BamHI, EcoRI, HindII, PstI, PvuII and TaqI digested genomic DNA probed with DP beta, DQ alpha, DQ beta and DR beta class II MHC gene probes. The RFLP patterns for 16 non-inhibitor and 11 inhibitor hemophiliac patients were analyzed. These 24 enzyme:probe combinations generated 231 fragments. Fifteen (15) fragments associated with the inhibitor phenotype; odds ratios ranged from 5.1 to 45 and lower bounds of 95% confidence intervals were > 1.000 for all 15 fragments. Five (5) fragments associated with non-inhibitors, with odds ratios ranging from 6.4 to 51.7. This report establishes a MHC related genetic basis for the inhibitor phenotype. No statistically significant differences in the distribution of serologically defined HLA-DR phenotypes were observed between the inhibitor and non-inhibitor groups.